2009
DOI: 10.2215/cjn.00790209
|View full text |Cite
|
Sign up to set email alerts
|

A Case for Water in the Treatment of Polycystic Kidney Disease

Abstract: Autosomal dominant polycystic disease (ADPKD) is an inherited disorder characterized by the development within renal tubules of innumerable cysts that progressively expand to cause renal insufficiency. Tubule cell proliferation and transepithelial fluid secretion combine to enlarge renal cysts, and 3-5-cyclic adenosine monophosphate (cAMP) stimulates that growth. The antidiuretic hormone, arginine vasopressin (AVP), operates continuously in ADPKD patients to stimulate the formation of cAMP, thereby contributin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
104
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 74 publications
2
104
0
1
Order By: Relevance
“…167 This strategy has been tested directly in the PCK rat, where high fluid intake sufficient to achieve a 3.5-fold increase in urine output by adding 5% glucose to drinking water reduced AVP excretion, renal expression of V2R, cAMP-dependent activation of the B-Raf/MEK/ERK, and attenuation of PKD. 168 It must be noted that the effects of increased water intake and V2R antagonists are not equivalent, even if they both reduce cAMP in the distal nephron and collecting ducts.…”
Section: High Water Intake In Adpkdmentioning
confidence: 99%
“…167 This strategy has been tested directly in the PCK rat, where high fluid intake sufficient to achieve a 3.5-fold increase in urine output by adding 5% glucose to drinking water reduced AVP excretion, renal expression of V2R, cAMP-dependent activation of the B-Raf/MEK/ERK, and attenuation of PKD. 168 It must be noted that the effects of increased water intake and V2R antagonists are not equivalent, even if they both reduce cAMP in the distal nephron and collecting ducts.…”
Section: High Water Intake In Adpkdmentioning
confidence: 99%
“…These cysts progressively expand and compress viable renal tissue, thereby causing renal insufficiency (1)(2)(3). For a long time there was no proven renoprotective treatment for this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Even forced-water ingestion sufficient to naturally suppress secreted vasopressin can slow cyst formation and enlargement (10). These observations led to emphatic recommendations that patients with ADPKD aim to ingest .3 liters of noncaffeinated fluid per day, with the hope that natural vasopressin suppression would attenuate cyst growth (11,12). In addition to vasopressin-mediated fluid transport into cysts, other studies have demonstrated that the disordered nephron epithelial cell proliferation is related to activation of mammalian target of rapamycin (mTOR), a protein kinase that regulates polycystin pathways, cell proliferation, and protein synthesis (13,14).…”
mentioning
confidence: 99%